Lovell and Winter's pediatric orthopaedics - Lovell, Wood W. 1915-; Weinstein, Stuart L.; Flynn, John M. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Now in its updated Seventh Edition, Lovell and Winter's Pediatric Orthopaedics remains a must-have for physicians and residents treating infants, children, and adolescents with orthopaedic problems. This classic, comprehensive reference covers the basic science, clinical manifestations, and management of orthopaedic problems in children. Now in full color, the foremost orthopaedists examine normal musculoskeletal development and the causes, diagnosis, and treatment of the entire range of abnormalities, with emphasis on evidence-based decision making in treatment selection. The clinical chapters include pearls and pitfalls and a description of the author's preferred approach. The book will now cover surgical techniques of management with step-by-step illustrations from the Atlas ofPediatric Orthopaedic Surgery